Characterizing Highly Effective Technology and Engineering Educators - Andrew John Hughes; Tyler S. Love; Kristine Dill (Education Sciences, 2023)
There have been numerous definitions and models proposed in attempts to better conceptualize effective educators; however, there is no consensus on a definition or model that characterizes effective educators in all contexts. Specific to technology and engineering (T&E) education, the Standards for Technological and Engineering Literacy (STEL) proposed three elements (core standards and benchmarks, T&E practices, and T&E contexts) for standardization of instruction to ensure more effective T&E educators. However, this requires educators to possess a broad spectrum of integrative knowledge and practices to guide authentic T&E teaching and learning experiences, something which the literature has shown is not always correlated with teaching experience. This article examines various definitions and characteristics of effective educators as presented throughout the literature considered within the context of T&E education. The information presented in this article has implications for helping educators, educator preparation programs, and professional development providers identify and develop competencies that the literature suggests can result in more effective T&E educators.